Fabrication and preliminary evaluation of the osteogenic potential for micro-/nano-structured porous BCP ceramics. Issue 4 (March 2020) - Wang, Jing; Su, Yangyang; Xu, Lizhou; Li, Danyang
Abstract: Nanoscale interface of biomaterials exhibits superiorities in promoting tissue repair and healing. Bioceramics are one of the most commonly used biomaterials for biological purposes such as tissue engineering. The fabrication of nanoscale ceramics with smart topography is essential for modulating cells in contact with such surface. In this research, a gas foaming method was employed to fabricate porous biphasic calcium phosphate (BCP) ceramics as substrates with a controllable component of hydroxyapatite/beta tricalcium phosphate (HA/β-TCP). Hydrothermal reaction was then introduced to modify the surface morphology of the substrates to obtain a nanoscale topography at different pH values and ionic microenvironments. Three kinds of ceramics (BCP; BCP with a nanoneedle-like surface, BNN; BCP covered with a hollow nanorod-like surface, BHN) were prepared with different surface morphologies and roughness, degradation properties and the phase composition during the hydrothermal process. All of them possessed an interconnected pore structure of macropores and micropores. Importantly, the nano-scale surface structure increased the total pore volumes as well as the micropore volumes, thus enhanced the specific surface area (SSA) and subsequent biological performance. Their biological behavior has also been assessed through a series of pivotal events, i.e. protein adsorption, cell attachment, proliferation, and osteogenic differentiation. Consequently, we found the nano-crystallization of the hollow nanorod-like structured and nanoneedle-like structured ceramic surface enhance the adsorption of both total serum proteins and BSA in vitro compared to the original BCP ceramics with micro-sized grains, as well as exhibit a more persistent release of BSA. Additionally, all the three ceramics have displayed excellent biocompatibilities for MSCs, and the morphology of ceramics played a decisive role in cells spreading and morphology, in which BNN showed the strongest effect to facilitate MSCs differentiation towards osteogenesis. Graphical abstract: Schematic illustration of the possible mode of surface topography involved osteogenic effect. Image 1